2016
DOI: 10.1111/jog.12960
|View full text |Cite
|
Sign up to set email alerts
|

Bone recurrence rarely seen in endometrial cancer and review of the literature

Abstract: The BR rate was remarkable in asymptomatic EC survivors. A single bone was frequently involved. Little is known of the optimal treatment for metastatic bone disease in EC, thus, management should be individualized and patients should be encouraged to participate in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…In some literature, the axial skeleton was the predominant metastatic sites [19,22,27], while some researchers insisted that most bone metastases of EC affected the appendicular skeleton [21,33]. Similar to Gunsu Kimyon's report [24], involvement of the axial (46%) and appendicular (54%) skeleton was almost equally observed in our study. It has been shown that 70% of cases had single localization bone recurrence and most patients had isolated bone metastases without extra-osseous spread [6,23].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In some literature, the axial skeleton was the predominant metastatic sites [19,22,27], while some researchers insisted that most bone metastases of EC affected the appendicular skeleton [21,33]. Similar to Gunsu Kimyon's report [24], involvement of the axial (46%) and appendicular (54%) skeleton was almost equally observed in our study. It has been shown that 70% of cases had single localization bone recurrence and most patients had isolated bone metastases without extra-osseous spread [6,23].…”
Section: Discussionsupporting
confidence: 85%
“…We further identi ed 20 studies [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] with a total of 24 cases of EC patients with bone metastases treated by surgery through literature research. The detailed information of the included studies is displayed in Table 2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Musculoskeletal metastasis has been rarely described. In case reports in the past 10 years, most musculoskeletal metastases were described with widespread metastatic disease, and rarely as an isolated metastasis ( Kimyon et al, 2016 , Ho et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…They describe a patient with FIGO stage IB grade I endometrial adenocarcinoma that developed a solitary recurrence in the sacrum that was amenable to surgical resection. In a study by Kimyon et al (2016) bone recurrence was seen, via imaging, in 10 of 162 endometrial cancer recurrence cases who underwent primary surgical management with/without adjuvant therapy. The most common site was the femur followed by the vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer Deng et al 2018 [18] NA NA NA Sehouli et al 2013 [19] NA NA NA Zhang et al 2013 [20] CD NA NA NA Zhang et al 2019 [21] NA NA NA Endometrial cancer Guo et al 2020 [22] NA NA NA Hong et al 2021 [23] NA NA NA Kimyon et al 2016 [24] NA NA NA Li et al 2020 [25] NA NA NA Liu et al 2020 [26] NA NA NA Mao et al 2020 [27] NA NA NA McEachron et al 2020 [28] NA NA NA Ouldamer et al 2019 [29] NA NA NA Takeshita et al 2016 [30] NA NA NA Uccella et al 2013 [31] NA NA NA Yoon et al 2014 [32] NA NA NA Uterine sarcoma Bartosh et al 2017 [33] NA NA NA Tirumani et al 2014 [34] NA NA NA Vulvar cancer Prieske et al 2016 [35] NA NA NA Cervical cancer Kanayama et al 2015 [36] NA NA NA Kocaer et al 2018 [37] NA NA NA Lin et al 2018 [38] NA NA NA Makino et al 2016 [39] NA NA NA Manders et al 2018 [40] NA NA NA Matsumiya et al 2016 [41] NA NA NA Nartthanarung et al 2014 [42] NA NA NA Sethi et al 2019 [43] NA NA NA Yin et al 2019 [44] NA NA NA Yoon et al 2013 [45] NA NA NA Zhang et al 2018 [46] NA NA NA Zhang et al 2020 [47] NA NA NA Zhou et al 2020 [48] NA NA NA Acknowledgments: This work was supported by IRCCS Istituto Ortopedico Rizzoli (Ricerca Corrente).…”
Section: Conflicts Of Interestmentioning
confidence: 99%